2018
DOI: 10.3389/fimmu.2018.00165
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcal Protein A Is a Key Factor in Neutrophil Extracellular Traps Formation

Abstract: Staphylococcus aureus are strong inducers of neutrophil extracellular traps (NETs), a defense mechanism of neutrophils against pathogens. Our aim was to explore the role of Protein A in S. aureus-induced NETosis. We determined the Protein A production of four different S. aureus strains and found a direct relationship between the degree of NETosis induction and Protein A production: strains producing higher concentrations of Protein A evoke significantly more NETs. A S. aureus strain in which Protein A as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 39 publications
0
32
0
1
Order By: Relevance
“…Although the majority of SpA is cell-anchored, 6.5% to 15% is secreted before sorting (O'Halloran et al, 2015) or released from the cell wall after enzymatic cleavage by LytM (Becker et al, 2014). We observed that the concentration of recombinant multi-domain SpA needed to decrease C1q deposition on an antigenic surface is lower than the amount reported to be secreted by Newman or USA300 strains in vitro (Hoppenbrouwers et al, 2018).…”
Section: Discussionmentioning
confidence: 63%
“…Although the majority of SpA is cell-anchored, 6.5% to 15% is secreted before sorting (O'Halloran et al, 2015) or released from the cell wall after enzymatic cleavage by LytM (Becker et al, 2014). We observed that the concentration of recombinant multi-domain SpA needed to decrease C1q deposition on an antigenic surface is lower than the amount reported to be secreted by Newman or USA300 strains in vitro (Hoppenbrouwers et al, 2018).…”
Section: Discussionmentioning
confidence: 63%
“…To confirm the role of SpA in promoting bacterial adhesion to vWF, we studied the attachment of the S. aureus Newman strain, known to largely express SpA (1517), onto vWF immobilized on microtiter wells. Wild-type (WT) bacteria adhered to vWF in large amounts, whereas bacteria from the Newman Δ spa strain lacking the adhesin did to a much lower extent (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The pneumonia-causing pathogen, Staphylococcus aureus ( S. aureus ), has also been detected in the airways of COPD patients (70, 71), notably in much older populations (72). This is particularly important because S. aureus can directly trigger NET formation (73), and might thus influence the cycle of pathogen–NETopathic inflammation in COPD. Despite there being high levels of NETs in the COPD airways, there is a deficiency in effective pathogen clearance.…”
Section: Pulmonary Pathogen-initiated Netopathic Inflammationmentioning
confidence: 99%